Vacuum hot pressed AZ31/UCF/AZ31 composite sheets: Microstructure and mechanical properties. (October 2017) - Nie, Huihui; Liang, Wei; Chen, Hongsheng; Hao, XinWei; Chi, Chengzhong; Li, Xianrong
Abstract: AZ31 Mg alloy/unidirectional carbon fiber (UCF)/AZ31 composite sheets were fabricated with AZ91 Mg alloy powder as an adhesive using vacuum hot pressing (VHP) at various temperatures. Both the wettability and bonding strength of the UCF/AZ91 interfaces increased with increasing VHP temperature, resulting in an improvement of the mechanical properties of the composite sheets. The fracture mechanism of the composite sheets at low VHP temperature (500 °C) was the pullout of UCFs and delamination. In contrast, at 560 °C, partial debonding between the UCFs and AZ91 was the dominant failure mechanism, and an S-type fracture path surrounding the UCFs was observed. The bonding strength of the UCF/AZ91 interface was weaker than that of the AZ91/AZ31 interface for this composite. The sheet prepared at 585 °C exhibited the largest ultimate tensile strength of 252 MPa and an elongation of 13.2%. This behavior was attributed to the enhancement of the interfacial bonding strength due to the formation of Al4 C3 and MgAl2 C2 phases at the UCF/AZ91 interface. The hardness and modulus reached maximum values of 9.9 and 61 GPa, respectively, near the UCF/AZ91 interface. Highlights: AZ31/UCF/AZ31 composite sheets was fabricated by vacuum hot pressing (VHP) method at different temperatures. The wettability and bonding strength of UCFs/AZ91 interfaces increased as the VHP temperature increased, which had beneficial effect on the mechanical properties of the sheets. The fracture mechanism at 500 °C was the pullout of UCFs and delamination. At 560 °C, partial debonding between UCFs and AZ91 was the dominant failure mechanism.